To PCR or not? The impact of shifting policy from PCR to rapid antigen tests to diagnose COVID-19 during the omicron epidemic: a nationwide surveillance study - Chi, Hsin; Chiu, Nan-Chang; Chen, Chung-Chu; Weng, Shun-Long; Lien, Chi-Hone; Lin, Chao-Hsu; Hu, Yao-Feng; Lei, Wei-Te; Tai, Yu-Lin; Lin, Liang-Yen; Liu, Lawrence Yu-Min; Lin, Chien-Yu (Frontiers in Public Health, 2023)
Background: COVID-19 had caused huge impacts worldwide. Polymerase chain reaction (PCR) is the mainstay diagnostic modality. In most hospitals in Taiwan, samples for PCR are collected at emergency department (ER) or outdoor clinics to avoid virus spread inside hospitals. Home rapid antigen test (RAT) is a feasible, low-cost, and convenient tool with moderate sensitivity and high specificity, which can be performed at home to reduce hospital visits. The diagnostic policy was altered from PCR to RAT, but the impact of diagnostic policy change remains unclear. Objectives: We conducted this study to investigate the number of COVID-19 cases, PCR testing, hospitalizations, mortalities, and hospital visits during the epidemic and evaluate the impact of diagnostic policy change. Methods: The diagnostic policy change was implemented in late May 2022. We used nationwide and hospital-based data of COVID-19 cases, PCR testing, hospitalizations, mortalities, and hospital visits before and after policy change as of 31Jul2022. Results: During the omicron epidemic, significant and synchronous increase of COVID-19 patients, PCR testing, hospital visits were observed. COVID-19 cases increased exponentially since April 2022 and the COVID-19 patients peaked in June (1943, 55571, and 61511 average daily new cases in April, May, and June, respectively). The PCR testing peaked in May (85788 daily tests) with high positive rate (81%). The policy of RAT as confirmatory diagnosis was implemented and a substantial decline of PCR testing numbers occurred. People hospitalized for COVID-19 peaked in June and decreased in July . The mortality cases also peaked in June. This trend was also validated by the hospital-based data with a significant decrease of emergency department visits and PCR testing. The proportion of people purely for PCR testing also decreased. Conclusions: The impact of diagnostic policy change was a complicated issue and our study demonstrated the huge impact of diagnostic policy on health seeking behavior. The PCR testing numbers and emergency department visits had substantial decrease after diagnostic policy change, and the plateau of epidemic peak eased gradually in approximate one month later. Widespread RAT application may contribute to the decreased hospital visits and preserve medical capacity. Our study provides some evidences.